1992
DOI: 10.7326/0003-4819-116-8-624
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid Treatment of Refractory Chronic Graft-versus-Host Disease of the Liver

Abstract: Therapy with UDCA was safe, well-tolerated, and efficacious in the short-term treatment of refractory chronic GVHD of the liver. Further investigation is needed to evaluate the long-term effects of UDCA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 24 publications
2
34
1
1
Order By: Relevance
“…In our series, immunosuppressive therapy led to normalisation of LFTs in all patients with C-GVHC as the only cause of CLD and to improvement in liver dysfunction in patients with multifactorial disease, although most of them required more than one treatment. UDCA, with or without immunosuppression, controlled hepatic C-GVHD, as previously reported by Fried et al, 32 but in contrast to their observations, our patients had a sustained response after cessation of therapy.…”
Section: Discussionsupporting
confidence: 70%
“…In our series, immunosuppressive therapy led to normalisation of LFTs in all patients with C-GVHC as the only cause of CLD and to improvement in liver dysfunction in patients with multifactorial disease, although most of them required more than one treatment. UDCA, with or without immunosuppression, controlled hepatic C-GVHD, as previously reported by Fried et al, 32 but in contrast to their observations, our patients had a sustained response after cessation of therapy.…”
Section: Discussionsupporting
confidence: 70%
“…In primary biliary sclerosis, ursodeoxycholic acid has improved liver function tests but not changed the natural history of the disease. 102 No long-term studies of this drug in chronic GVHD have been reported.…”
Section: Minimize Effects On Target Tissuesmentioning
confidence: 99%
“…In PBC and liver allograft rejection treatment with ursodeoxycholic acid (UDCA) has been shown to delay progression of the disease . It is therefore not surprising that UDCA was tested for treatment of refractory hepatic GVHD in adults after allogeneic BMT (Fried et al, 1992). The additional use of UDCA has not yet been described in SCID.…”
mentioning
confidence: 99%